Pengembangan Pembelajaran Digital pada Mata Pelajaran Pendidikan Agama Islam Berbasis Nilai Adab dan Akhlak Islami - Kaimudin Kaimudin; Nurhasan Nurhasan; Yudi Aris Dwiyanto (CV. Lentera Literasi Indonesia, 2026)
Rapid progress in digital technology has profoundly reshaped teaching and learning processes. Nevertheless, the application of digital tools in Islamic Religious Education (known as Pendidikan Agama Islam or PAI) has largely prioritized knowledge acquisition and technical proficiency, often overlooking the crucial development of adab (proper conduct) and akhlak (Islamic moral character), which form the core of Islamic education. This study explores various digital innovations in PAI instruction that are rooted in Islamic principles of adab and akhlak, along with their effects on shaping students’ moral character. Employing a qualitative library research approach, the study draws on recent scholarly journals, reference books, and academic publications. The analysis reveals that carefully structured digital resources such as exemplary moral videos, gamified activities infused with Islamic values, moderated online ethical forums, virtual reality simulations for practicing etiquette, and morally oriented educational social media contentcan effectively foster ethical values. The effectiveness of these approaches relies heavily on the balanced fusion of technological tools, pedagogical strategies, and Islamic content centered on nurturing adab.